Interleukin-15 in the treatment of cancer - Waldmann, Thomas A (Expert Rev Clin Immunol, 2014)
IL-15 is a 14–15 kDa member of the four α-helix bundle of cytokines that acts through a heterotrimeric receptor involving IL-2/IL-15R β, γc and the IL-15 specific receptor subunit IL-15R α. IL-15 stimulates the proliferation of T, B and NK cells, and induces stem, central and effector memory CD8 T cells. In rhesus macaques, continuous infusion of recombinant human IL-15 at 20 μg/kg/day was associated with approximately a 10-fold increase in the numbers of circulating NK, γ/δ cells and monocytes, and an 80- to 100-fold increase in the numbers of effector memory CD8 T cells. IL-15 has shown efficacy in murine models of malignancy. Clinical trials involving recombinant human IL-15 given by bolus infusions have been completed and by subcutaneous and continuous intravenous infusions are underway in patients with metastatic malignancy. Furthermore, clinical trials are being initiated that employ the combination of IL-15 with IL-15R α(+/−) IgFc.